Anorectal Injuries due to Foreign Bodies: Case Reports and Review of the Management Options - Faruk Karateke; Koray Das; Sefa Ozyazici; Ebru Menekse; Zikret Koseoglu; Ozgur Karcioglu (Case Reports in Surgery)
Anorectal injuries due to autoerotic activity with rectal foreign bodies were identified in four male patients. The objects were bottle in one patient, glasses in two patients, and showerhead in one patient. Foreign bodies were extracted within lithotomy position after anal dilatation, under general anesthesia in 3 patients. One patient presented with peritoneal irritation and had a diagnosis of rectal perforation. He underwent transanal rectal repair with proximal fecal diversion. In this paper we described 4 patients who had anorectal injuries due to autoerotic activity with foreign bodies and reviewed the management options in literature.